Count Karlstein - Pullman, Philip, 1946- (New York : Knopf : Distributed by Random House, 1998)
In the mountains of Switzerland the wicked Count Karlstein plots to abandon his two orphaned nieces in a hunting lodge as prey for the Demon Huntsman and his ghostly hounds.
Keywords: Orphans -- Fiction; Uncles -- Fiction; Adventure and adventurers -- Fiction; Switzerland -- Fiction